POLEMIK PROGRAM VAKSINASI DI INDONESIA: STUDI ATAS PEMBERITAAN MEDIA MASSA - Mukti Abdul Gani; Maulidatun Hasanah; Ibnu Alryansah; Siti Eka Nurmala; Diah Kumalasari; Yusuf Fadli (Universitas Islam Darul Ulum Lamongan, 2022)
Covid-19 pandemic has given rise to a variety of new phenomena. One of them is a social phenomenon, regarding the emergence of anti-vaccine groups in various countries, including Indonesia. In this journal writing describes vaccinations and the implementation of government vaccination policies.The study in this journal aims to complement the shortcomings of previous research on specific polemics, which will map and identify the shape and form of the pros and cons of vaccines in society. The method used is a qualitative approach with a descriptive analytic approach. The research data obtained are then analyzed and interpreted to see the extent of the polemic of vaccination carried out by the Indonesian government. The study in this journal aims to complement the shortcomings of previous research on specific polemics, which will map and identify the shape and form of the pros and cons of vaccines in society.